Rosacea, microbiome and probiotics: the gut-skin axis - Sánchez-Pellicer, Pedro; Eguren-Michelena, Cristina; García-Gavín, Juan; Llamas-Velasco, Mar; Navarro-Moratalla, Laura; Núñez-Delegido, Eva; Agüera-Santos, Juan; Navarro-López, Vicente (Frontiers in Microbiology, 2024)
Rosacea is an inflammatory skin disease involving diverse symptoms with a variable clinical progress which can severely impact the patient's quality of life as well as their mental health. The pathophysiological model of rosacea involves an unbalanced immune system predisposed to excessive inflammation, in addition to vascular and nervous alterations, being certain cutaneous microorganisms' triggers of the symptoms onset. The gut-skin axis explains a bidirectional interaction between skin and gut microbiota in some inflammatory skin diseases such as atopic dermatitis, psoriasis, or rosacea. The introduction and consolidation of the next-generation sequencing in recent years has provided unprecedented information about the microbiome. However, the characterization of the gut and skin microbiota and the impact of the gut-skin axis in patients with rosacea has been little explored, in contrast to other inflammatory skin diseases such as atopic dermatitis or psoriasis. Furthermore, the clinical evolution of patients with rosacea is not always adequate and it is common for them to present a sustained symptomatology with frequent flare-ups. In this context, probiotic supplementation could improve the clinical evolution of these patients as happens in other pathologies. Through this review we aim to establish and compile the basics and directions of current knowledge to understand the mechanisms by which the microbiome influences the pathogenesis of rosacea, and how modulation of the skin and gut microbiota could benefit these patients.